Deskripsi Tingkat Berpikir Visual dalam Memahami Definisi Formal Barisan Bilangan Real Berdasarkan Gaya Kognitif Mahasiswa Makassar - Wahidir Ali; Ilham Minggi; Usman Mulbar (Issues in Mathematics Education (IMED), 2017)
The purpose of this study is to describe the level of visual thinking in understanding the formal definition of real numbers sequence based on cognitive style of Field Independent type and also cognitive style of Field Dependent type of students in Mathematis Department of UNM. Visual thinking is one of the abilities that becomes the bridge for transforming information from abstract-verbs to clearer forms. Wileman (Stoke, 2001) defines visual thinking as the ability to convert information of all kinds into images, graphics, or other forms that can help communicate information. The research method used in this research is descriptive research method design. The level of visual thinking is measured by using a test instrument with a special indicator measuring the level of visual thinking. The subject of this study consisted of two persons representing the type of cognitive style, the Field Dependent type cognitive style (FD) with the Field Independent cognitive style (FI). The results of this study show the location of the shortcomings and advantages of students in visual thinking on each type of cognitive style. In addition, it is found that there is a relationship between the level of visual thinking with the thinking style of the students in Mathematics Department of UNM.